Amazoniaseius imparisetosus n. sp., n. g.: an unusual new phytoseiid mite (Acari: Phytoseiidae) from the Amazon forest - Demite, Peterson R.; Cruz, Wilton P. Da; Mcmurtry, James A.; de Moraes, Gilberto J. (Zootaxa, 2017)
A new genus and species of the subfamily Typhlodrominae are described from the Brazilian Amazon. The main differences between this and all other phytoseiid species are the presence of two unpaired setae on dorsal shield of deutonymphs and adults, and the absence of all ZV setae. It also differs from other typhlodromine species by its relatively long J5 setae, the presence of seta J4 and the broadly rounded posterior margin of the genital shield. Thus, the unique idiosomal setal pattern of this species is here designated as 13A+x:8F+X/JV-3,4:ZV-1–3. Because of the unique characteristics, we here describe this new taxon, Amazoniaseius imparisetosus n. sp., n. g., based on protonymphs, deutonymphs and adult females. This species is accommodated in tribe Paraseiulini Wainstein within Typhlodrominae, due to the presence of the setae z6 and S4. The tribe is redefined and an updated dichotomous key for the separation of the genera of Paraseiulini is provided.